2003
DOI: 10.1094/cchem.2003.80.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hard Vitreous Kernels in Durum Wheat by Machine Vision

Abstract: Cereal Chem. 80(5):511-517An imaging method that detects nonvitreous regions in sound kernels of durum wheat at high speed is described. Kernels are analyzed simultaneously for individual vitreousness and individual kernel size and shape are measured concurrently. The measurement of 500 kernels per sample is adequate for highly reproducible results. Significant agreement was found between inspector-determined hard vitreous kernel percentages (HVK) and machine-determined HVK scores for export cargo samples of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…The great potential of machine vision to assess the physical properties of grains was demonstrated with respect to characterizing the vitreousness of wheat (Shatadal et al 1998) and endosperm hardness (Konopka et al 2005). The degree of vitreousness of durum wheat was also examined by Symons et al (2003), with the help of machine vision. The results were well correlated with those of human inspection.…”
Section: Introductionmentioning
confidence: 99%
“…The great potential of machine vision to assess the physical properties of grains was demonstrated with respect to characterizing the vitreousness of wheat (Shatadal et al 1998) and endosperm hardness (Konopka et al 2005). The degree of vitreousness of durum wheat was also examined by Symons et al (2003), with the help of machine vision. The results were well correlated with those of human inspection.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by many several authors, the fluorescence in Region 2 (excitation near 360 nm and emission near 420 nm) can be ascribed to the presence of ferulic acid in wheat milling fractions [18,19,24]. Obviously, the addition of ferulic acid in the dough recipes causes an increase of fluorescence in this region (dough f, fg, fG and fgG).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, gluten proteins through their contents in tyrosine and tryptophan residues, ferulic acid and possibly tocopherols, glycoflavones and riboflavine have been characterized as fluorescent compounds [15][16][17][18][19][20][21][22][23][24][25][26]. To our knowledge, the only studies devoted to the dough fluorescence properties have been carried out by Bonomi et al [27], Hushka et al [28] Kokawa et al [29,30].…”
mentioning
confidence: 99%
“…Indeed, temperature and light intensity during grain filling and the rate of grain drying (Parish and Halse 1968) were pointed out as affecting another characteristic of the endosperm texture known as vitreousness. Differences in vitreousness could be determined visually by the level of translucence or through newly developed methods such as a machine vision (Symons et al 2003) or dual energy X-ray imaging (Neethirajan et al 2007), as demonstrated with durum wheats.…”
Section: A Study Of Puroindoline B Gene Involvement In the Milling Bementioning
confidence: 99%